Diagnostic utility of intravoxel incoherent motion mr imaging in differentiating primary central nervous system lymphoma from glioblastoma multiforme. Issue 5 (19th April 2016) - Yamashita, Koji; Hiwatashi, Akio; Togao, Osamu; Kikuchi, Kazufumi; Kitamura, Yoshiyuki; Mizoguchi, Masahiro; Yoshimoto, Koji; Kuga, Daisuke; Suzuki, Satoshi O.; Baba, Shingo; Isoda, Takuro; Iwaki, Toru; et al.
Abstract : Purpose: To evaluate the diagnostic performance of intravoxel incoherent motion (IVIM) MR imaging and 18 F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) in differentiating primary central nervous system lymphoma (PCNSL) from glioblastoma multiforme (GBM). Materials and Methods: Fifty patients, 17 with PCNSL and 33 with GBM, were retrospectively studied. From the 3 Tesla IVIM data, the perfusion fraction (f) and diffusion coefficient (D) were obtained. In addition, the maximum standard uptake value (SUVmax ) was obtained from the FDG‐PET data. Each of the three parameters was compared between PCNSL and GBM using Mann‐Whitney U‐test. The performance in discriminating between PCNSL and GBM was evaluated using receiver‐operating characteristics analysis and area‐under‐the‐curve (AUC) values for the three parameters. Results: The fmax and Dmin values were significantly higher in GBM than in PCNSL ( P < 0.01 and P < 0.0001, respectively). In addition, the SUVmax value was significantly lower in GBM than in PCNSL ( P < 0.0005). The AUC values for fmax, Dmin, and SUVmax were 0.756, 0.905, and 0.857, respectively. The combination of the fmax and Dmin increased the diagnostic performance (AUC = 0.936) of fmax ( P < 0.05), but this value was not significantly different from the values for Dmin ( P = 0.30). Conclusion: IVIM‐MR imaging noninvasively provides useful quantitative information in distinguishing between PCNSL and GBM. J. Magn. Reson. Imaging 2016;44:1256–1261.